2016
DOI: 10.1103/physreva.93.063405
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the electron multiple recollision dynamics in intense laser fields with Bohmian trajectories

Abstract: Electron multiple recollision dynamics under intense mid-infrared laser fields is studied by means of the De Broglie-Bohm's framework of Bohmian mechanics. Bohmian trajectories contain all the information embedded in the time-dependent wave function. This makes the method suitable to investigate the coherent dynamic processes for which the phase information is crucial. In this study, the appearance of the sub-peaks in the high harmonic generation timefrequency profiles and the asymmetric fine structures in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…This result strongly supports the use of the classical trajectory in the semiclassical trajectory method to describe the motion of an ionized electron. [22][23][24][25]86] Very recently, in the Bohmian scenario, Jooya et al [87] and Li et al [88] found the laser-driven electron-multirescattering trajectories, which is consistent with the commonly accepted multi-return trajectories of the ionized electron calculated by the semiclassical trajectory method. Coulomb potential, and quantum potential) of one Bohmian trajectory with the initial position of 𝑟 0 .…”
Section: Study Of the Electron Dynamics After Tunneling Ionizationsupporting
confidence: 65%
“…This result strongly supports the use of the classical trajectory in the semiclassical trajectory method to describe the motion of an ionized electron. [22][23][24][25]86] Very recently, in the Bohmian scenario, Jooya et al [87] and Li et al [88] found the laser-driven electron-multirescattering trajectories, which is consistent with the commonly accepted multi-return trajectories of the ionized electron calculated by the semiclassical trajectory method. Coulomb potential, and quantum potential) of one Bohmian trajectory with the initial position of 𝑟 0 .…”
Section: Study Of the Electron Dynamics After Tunneling Ionizationsupporting
confidence: 65%
“…The secondary collisions correspond to those trajectories, which do not recombine in the first return; rather, the electron scatters and returns to the parent core when again the field changes sign. The reduced harmonic emission is attributed to the higher spread of the wave packet for the second revisiting electron, as also corroborated in [47][48][49][50]. The time-frequency analysis of the HHG spectra corresponding to the bi-chromatic driver is presented in figure 1(d).…”
Section: Hhg By Bi-chromatic Field With ωsupporting
confidence: 62%
“…The present study is devoted to a description of tunneling ionization employing Bohmian Mechanics [11][12][13], which has recently attracted much attention [14][15][16][17][18][19][20][21][22][23][24]. It will be shown that computing the streamlines of the wavefunction probability over time provides valuable insights and a natural route to understanding complex ultrafast mechanisms.…”
Section: Introductionmentioning
confidence: 99%